IMPLIKASI PELAKSANAAN PROGRAM LITERASI KEAGAMAAN UNTUK MENUMBUHKAN MINAT MEMBACA AL-QUR’AN PADA SISWA KELAS III DI MADRASAH IBTIDAIYAH SWASTA AT-TAQWA SAMBAS - Natasya Natasya; Rusiadi Rusiadi; Syaifuddin Syaifuddin (JIP: Jurnal Ilmu Pendidikan, 2023)
This research is motivated by indications that the religious literacy program of the At-Taqwa Sambas Private Madrasah Ibtidaiyah is slightly different from the religious literacy program of reading the Koran at other schools, because the At-Taqwa Sambas Private Madrasah Ibtidaiyah is held on Monday-Saturday, on before the start of learning at 07:00-07:30 WIB, this activity took place half an hour before the start of the first lesson and was also based on the findings in the initial interview that class III students were very less fluent in reading the Al-Qur'an because they did not memorize the hijaiyah letters. and short lengths of Al-Qur'an reading, this was indicated by 25 students still using iqra (small Al-Qur'an). This research has three research objectives, including the following: First, to find out the program for implementing Al-Qur'an Reading at the At-Taqwa Sambas Private Madrasah Ibtidaiyah. Second, to find out the steps for implementing reading the Koran at the At-Taqwa Sambas Private Madrasah Ibtidaiyah. Third, to determine the supporting and inhibiting factors for the religious literacy program to foster interest in reading the Al-Qur'an at the At-Taqwa Sambas Private Madrasah Ibtidaiyah. This research uses a qualitative approach while this type of research is phenomenological research. There are three types of data collection techniques in this research, namely: Interview, Observation and Documentation. Meanwhile, the data analysis techniques used are data collection, data reduction, data display, drawing conclusions and verification. Then the data validity checking techniques used are triangulation (source triangulation) and member check. The research results are: First, religious literacy programs to foster interest in reading the Al-Quran in class III students include; 1). BTQ (Read and Write Al-Qur'an). 2). Tahfidz (Memorization of the Qur'an). 3). Muhadarah (Short Lecture by students). 4). Congregational noon. 5). Duha Prayer (Each class). Second, the implementation of a religious literacy program to foster interest in reading the Al-Quran in class III students including: a). The activity begins by reading the surahs Al-Fatihah, Ad-Dhuha, AlInsyirah, and Asy Syam. Then read study prayers, pillars of faith, pillars of Islam, asmaul husna, and the last activity is reading and writing the Koran. b). Al-Qur'an reading activities at the At-Taqwa Sambas Private Madrasah Ibtidaiyah using the face to face method with students. The Al-Qur'an reading activity in class III is divided into two groups, there are Al-Qur'an juz and small groups, then in this activity the teacher gives directions first to continue reading to the next page while the teacher checks the punctuation (tajwid) and makharijul letters to assess fluency in reading the Koran. Third, the supporting factors for religious literacy programs are supportive facilities, skilled teachers, and a good role of parents. Meanwhile, the inhibiting factor for religious literacy programs is that reading habits have not become a priority for students, many students play while reading the Al-Qur'an.